P613 Comparative objective effectiveness of vedolizumab and ustekinumab in a real-life cohort of active Crohn's disease patients failure to TNF inhibitors. (21st January 2022) - Onali, S; Pugliese, D; Caprioli, F A; Orlando, A; Biancone, L; Nardone, O M; Imperatore, N; Fiorino, G; Cappello, M; Viola, A; Principi, M B; Bezzio, C; et al.
Abstract: Background: The use of ustekinumab (UST) and vedolizumab (VDZ) as second line therapy in Crohn's disease (CD) patients failing tumour necrosis factor alpha inhibitors is still debated. The aim of the study was to compare in a large multicentre observational retrospective cohort, the effectiveness of UST and VDZ as second line therapy as assessed by clinical and objective outcomes including endoscopy and gastro intestinal (GI)-imaging. Methods: Clinical response, remission and steroid-free remission at week 26 and 52 were evaluated in a retrospective cohort of CD patients previously experienced TNF-alpha inhibitors (primary or secondary failure, and intolerant). Objective response and remission were evaluated by one or more techniques including ileocolonoscopy, magnetic resonance (MR)/computer tomography (CT) enteroclysis and small bowel ultrasound (US) performed within 3 months before the beginning of the treatment and after one year of therapy. Inverse propensity of treatment weighting (IPTW) and propensity score matching (PMS) methods were used for statistical analysis. Results: 470 CD patients (239 UST and 231 VDZ) were included in the study. At week 26 clinical response, clinical remission and steroid free remission were similar between the two groups (Figure 1) At week 52, clinical remission and steroid-free remission rates were significantly higher in VDZ-treated patients (clinical remission: UST 42.5% vs VDZ 55.5%, p=0.01; steroid-free clinical remission UST 40.6% vs VDZ 51.1%, p=0.038; Figure 1). 302 patients (135 UST and 167 VDZ) had objective evaluation of disease activity at baseline and week 52. At week 52 objective response and remission rates were similar between the groups. (Figure 2). Clinical response at week 26 predicted steroid-free remission at week 52 in both UST- and VDZ-treated patients. Safety profiles were similar between the two groups. Conclusion: One-year treatment with VDZ was associated with higher rate of clinical remission as compared to UST, but no difference was observed between the two groups when objective outcomes were investigated